Advancing oral health policy for mandatory dental screening before admission into public primary and secondary schools in Lagos, Nigeria - Oyapero, Afolabi (J Family Med Prim Care, 2020)
BACKGROUND: The oral health of children is a significant public health issue that considerably affects nutritional intake, growth and development, daily learning activities, sleep pattern, self-esteem, and quality of life. In Nigeria, limited progress has been made in reducing the prevalence and burden of oral health problems such as dental caries, Noma, and oral cancer due to absence of national data, inadequate budgetary allocation, dearth of personnel, poor policy framework/implementation, and challenges of care access. Lagos state has a large, diverse population, hampered by illiteracy and poverty, and school-based dental screening is a strategy that can potentially reduce the prevalence of oral diseases among a vulnerable population in resource-poor settings. This document proposes secondary prevention through screening for a significant proportion of children in Lagos State and will be a veritable source of Data for oral Health planning. PROPOSED INTERVENTIONS: A draft policy document is proposed for the Ministry of health for legislation mandating a low-cost comprehensive oral health examination to screen every child admitted into Primary or Secondary School in any of the State Government-owned Schools in Lagos State. Each child will receive an oral health education leaflet and a duplicated annual dental screening form in addition to all the other requirements he will provide before being cleared for resumption when the academic year commences. The parents of the child will then be expected to present the form at any of the Lagos State-owned General hospitals for dental screening. The children will receive expedited attention and will not be kept waiting unnecessarily before being attended to. Students who have any form of dental disease will however be required to open a dental card at the clinic and have their treatments done as soon as possible. Except the dental treatment is found to be very expensive, the parents would be firmly encouraged to have the treatment done before the academic year commences and the form can be filled and signed. The school authorities would be notified if the parents cannot bear the cost and the ministry of health would be duly informed. Once the child is examined and found to be free of dental disease, the form can be filled and signed by the attending dental practitioner and duly stamped. A duplicate would be retained in a dedicated file in the dental clinic while the main form will be returned to the school. The schools will keep the forms in a dedicated file and at the end of each admission cycle, a report on the oral health status of the children for each school must be submitted to the Ministries of Education and Health. The preferred format for submission should be an excel spreadsheet containing the biodata and the summary of dental findings and treatment provided as applicable for each child. EVALUATION: Short and long term evaluation will be done to assess coverage rate, the number of dental diseases identified, number of treatments done, the satisfaction of parents and children with the services while the cost-benefit analysis of the services will be determined using a combination of qualitative and quantitative methods. The results of these analyses will be utilized to justify further government commitment of resources to this program. CONCLUSION: Strategies to reduce the burden of disease in developing countries must focus on policy design/implementation and preventive interventions. This proposed policy can help to decrease or eliminate barriers to access. It can also increase the number of children who will receive both preventive and curative oral care and also improve their knowledge of oral health.